Association of Dietary Vitamin K Intake With Cognition in the Elderly - Wang, Anni; Zhao, Meng; Luo, Jia; Zhang, Tianhao; Zhang, Dongfeng (Frontiers in Nutrition, 2022)
Several previous studies discussed the association between vitamin K (VK) status and cognition. But the association between dietary VK consumption and cognitive performance in the elderly was not well understood. Therefore, we investigated the correlation between dietary VK intake and the cognition of the elderly. Our research used the data of the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014. The dietary intake of VK was assessed by two 24-hour dietary recalls. The cognitive function was measured in the survey of NHANES, including the Consortium to Establish a Registry for Alzheimer’s disease Word Learning subtest (CERAD W-L), Animal Fluency test (AFT), and Digit Symbol Substitution Test (DSST). Logistic regression and restricted cubic spline models were applied to assess the relationship between dietary VK intake and cognition. Compared with the lowest dietary VK intake group, the multivariate-adjusted odds ratio (95% confidence interval) of the highest intake group was CERAD W-L score of 0.39 (0.26–0.60), AFT score of 0.59 (0.38–0.92), and DSST score of 0.44 (0.29–0.65), respectively. There was an L-shaped dose-response relationship between dietary VK intake and CERAD W-L score. There was a linear dose-response relationship between dietary VK intake and AFT score, and there was also a linear dose-response relationship for the DSST score. In addition, we also found a negative association between VK from vegetables and the risk of low CERAD W-L scores. Dietary VK intake and VK intake from vegetables were inversely related to the risk of low cognitive performance of the elderly.